2006
DOI: 10.1038/sj.jid.5700454
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Expression of Specific Biomarkers Distinguish Human Beard from Scalp Dermal Papilla Cells

Abstract: Androgen exposure stimulates the growth of beard hair follicles. The follicle dermal papilla appears to be the site of androgen action; however, the molecular mechanisms that regulate this process are not well understood. In an attempt to identify genes that contribute to the androgen-responsive phenotype, we compared gene expression patterns in unstimulated and androgen-treated cultured human dermal papilla cells isolated from beard (androgen-sensitive) and occipital scalp (androgen-insensitive) hair follicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 73 publications
3
33
0
Order By: Relevance
“…S2). Rutberg et al reported SFRP2 as a signature gene of beard (B) DP cells that distinguishes them from scalp DP cells (9). In agreement with their finding, SFRP2 mRNA levels were significantly higher in beard DP cells and were barely detectable in frontal balding (F) DP cells (Fig.…”
Section: Resultssupporting
confidence: 77%
“…S2). Rutberg et al reported SFRP2 as a signature gene of beard (B) DP cells that distinguishes them from scalp DP cells (9). In agreement with their finding, SFRP2 mRNA levels were significantly higher in beard DP cells and were barely detectable in frontal balding (F) DP cells (Fig.…”
Section: Resultssupporting
confidence: 77%
“…One example, in human skin, is the observation that androgens stimulate hair follicle growth in the face but cause follicle miniaturisation in the scalp. DP cells express androgen receptors and 5a-OH-reductase -a key enzyme in androgen metabolism -and DP from different body sites differ in their responsiveness to androgen (Rutberg et al, 2006).…”
Section: Dermal Papilla Heterogeneitymentioning
confidence: 99%
“…Follicles from frontal and parietal areas of the human scalp are considered to be androgen-sensitive. There are also two more types of hair follicles: androgen-independent hair follicles, such as eyelashes, and androgen-dependent pigmented terminal hair follicles, such as beard [26,29,30]. Why do hair follicles have different sensitivity to androgens is still open question.…”
Section: Hair Follicle-related Signaling Pathways In Androgenic Alopeciamentioning
confidence: 99%
“…Besides oligonucleotide microarray experiments, microRNAs differential expression analysis was conducted in balding and nonbalding dermal papilla cells [32]; the expression of sex-determining genes in bald frontal scalp area was examined by real-time RT-PCR [80]. Also, microarray analysis to find differences in expression between beard and scalp dermal papilla cells is available [30].…”
Section: Pathway Analysis Of Microarray Experimental Data In Agamentioning
confidence: 99%
See 1 more Smart Citation